Extensive fournier gangrene with retroperitoneal involvement in a diabetic patient - Girieasen, M. Sabari; Viswanathan, Naveenkumar; Nedunchezhian, S.; Ross, Kannan (International Surgery Journal, 2020)
Fournier’s gangrene is a rare, rapidly progressive, fulminant form of necrotizing fasciitis of the genital, perianal and perineal regions extending to the abdominal wall between the fascial planes. It is secondary to polymicrobial infection by aerobic and anaerobic bacteria with a synergistic action. A 42 year old male who is an alcoholic and diabetic on irregular treatment presented with scrotal swelling and pain for 5 days following a trauma. On examination, patient was febrile, tachypneic and had tachycardia. His scrotum was edematous and erythematous on right side with crepitus. Abdomen was warm on right side till umbilicus and had crepitus. He was in sepsis and had diabetic ketoacidosis, prerenal azotemia and mild impairment of liver function. A diagnosis of extensive Fournier gangrene with retroperitoneal involvement was made. Patient underwent scrotal exploration and aggressive debridement serially. Testis was spared. As patient improved with good wound care and glycemic control, wound was closed. Though our patient had retroperitoneal involvement without peritonitis, he was deferred laparotomy which significantly reduced the morbidity and mortality. It is one of the few reported case in the literature with retroperitoneal involvement.